LWiSSy: uma linguagem específica de domínio para modelagem de sistemas de redes de sensores e atuadores sem fio - Dantas, Priscilla Victor (2012)
The field of Wireless Sensor and Actuator Networks (WSAN) is fast increasing and has attracted the interest of both the research community and the industry because of several factors, such as the applicability of such networks in different application domains (aviation, civil engineering, medicine, and others). Moreover, advances in wireless communication and the reduction of hardware components size also contributed for a fast spread of these networks. However, there are still several challenges and open issues that need to be tackled in order to achieve the full potential of WSAN usage. The development of WSAN systems is one of the most relevant of these challenges considering the number of variables involved in this process. Currently, a broad range of WSAN platforms and low level programming languages are available to build WSAN systems. Thus, developers need to deal with details of different sensor platforms and low-level programming abstractions of sensor operational systems on one hand, and they also need to have specific (high level) knowledge about the distinct application domains, on the other hand. Therefore, in order to decouple the handling of these two different levels of knowledge, making easier the development process of WSAN systems, we propose LWiSSy (Domain Language for Wireless Sensor and Actuator Networks Systems), a domain specific language (DSL) for WSAN. The use of DSLs raises the abstraction level during the programming of systems and modularizes the system building in several steps. Thus, LWiSSy allows the domain experts to directly contribute in the development of WSANs without having knowledge on low level sensor platforms, and network experts to program sensor nodes to meet application requirements without having specific knowledge on the application domain. Additionally, LWiSSy enables the system decomposition in different levels of abstraction according to structural and behavioral features and granularities (network, node group and single node level programming)